2006
DOI: 10.29333/ejgm/82355
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Enterobius Vermicularis Infection And Nocturnal Enuresis

Abstract: Aim:The possible association between certain childhood infections and the propensity to develop nocturnal enuresis may include intestinal helminth infections. Objective: To explore the association between Enterobius vermicularis and nocturnal enuresis among children 4 to 7 years of age in a Turkish orphanage.Methods: Eighty children (45 boy, 35 girl, age range 4-7 years) participated in this study. The association between Enterobius vermicularis and enuressis was investigated after mebendazole therapy in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…Other symptoms include abdominal discomfort, loss of appetite, weight loss, insomnia, restlessness, irritability (Vermund & Wilson, 2000;Burkhart & Burkhart, 2005). Occasionally pinworm infection may cause enuresis (Çulha & Duran, 2006;Otu-Bassey et al 2011), urinary tract infections (Zahariou et al, 2007;Ayala Castellanos Mde et al, 2009) or appendicitis (Arca et al, 2004;Ramezani & Dehghani, 2007;Panidis et al, 2011). Epidemiological studies from different European countries reveal that enterobiasis prevalence showed a declining trend at the end of the 20 th century, although it has remained relatively common in children populations (Gauert, 1998;Gale, 2002;Bitkowska et al 2004;Crotti & D'Annibale, 2006;Remm, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms include abdominal discomfort, loss of appetite, weight loss, insomnia, restlessness, irritability (Vermund & Wilson, 2000;Burkhart & Burkhart, 2005). Occasionally pinworm infection may cause enuresis (Çulha & Duran, 2006;Otu-Bassey et al 2011), urinary tract infections (Zahariou et al, 2007;Ayala Castellanos Mde et al, 2009) or appendicitis (Arca et al, 2004;Ramezani & Dehghani, 2007;Panidis et al, 2011). Epidemiological studies from different European countries reveal that enterobiasis prevalence showed a declining trend at the end of the 20 th century, although it has remained relatively common in children populations (Gauert, 1998;Gale, 2002;Bitkowska et al 2004;Crotti & D'Annibale, 2006;Remm, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…O parasito tem sido associado também com casos agudos de apendicite, colite e gastrenterites (29,30). Quando localizados no trato geniturinário, por exemplo, a infecção por E. vermicularis pode causar a enurese noturna, entre outras complicações (4,5,21).…”
unclassified